Role of serum Zinc and Copper levels in patients with acne vulgaris - Butool, Fouqiya; Mohammed, Amanullah; Syed, Parween Ali; Mohammed, Rasheed Abdul (Journal of Orofacial Research, 2019)
Background: Acne vulgaris is a disorder in which hair follicles develop obstructing horny plugs (comedones) and the reason is unknown. The aim of the present study was to assess the relationship of zinc and copper to Acne vulgaris. Material and Methods: Young female patients in the age group of 13 to 19 years, with the problem of acne attending the out-patient department of Dermatology of a tertiary teaching general hospital over a period of six months, were included in this study. Female attenders (friends) of the patients of the same age, without acne comprised of the control group. Group 1 consisted of 50 patients with acne and group 2 was a control group having 25 normal individulas. The blood samples of patients and controls were collected on the scheduled date and analysed for serum zinc and copper levels at National Institute of Nutrition, Hyderabad by Atomic absorption spectrometry. Results: Mean Serum zinc levels in patients was 24.4 ? 2.4 whereas the levels in controls was 99.4 ? 4.5. The observation is that the mean value in acne patients is statistically significant and lower than controls (p